To find the nth term in this sequence, we can see that the pattern is increasing by 3 each time. So, the nth term can be found by adding 3*(n-1) to the first term.
For example, the 1st term is 17. So, the formula for the nth term is:
nth term = 17 + 3*(n-1)
Now, to find "a's answer", we need to find the value of the 10th term in the sequence.
Using the formula above:
10th term = 17 + 3*(10-1)
= 17 + 3*(9)
= 17 + 27
= 44
Therefore, "a's answer" is 44.
what is the n^th term
what is a's answer
n^th term is:
n (position in sequence) 1 2 3 4 10
value of term 17 20 23 26 a
1 answer